Externalizing Metaphors Therapy and Innovative Moments: A Four-Session Treatment Group for Anxiety. Issue 3 (3rd July 2018) - McGuinty, Everett F.; Bird, Brian M.; Silva, Joana R.; Morrow, Danielle K.; Armstrong, David C.
ABSTRACT: The zeitgeist for brief services psychotherapy efficacy is well underway within the individual and family therapy treatment modalities. However, this paradigm shift, to produce clinically significant mental health outcomes in a much shorter time, has evolved to a much lesser degree within the treatment group format. Longer-term treatment group protocols typically do not match treatment-seeking behaviors with high dropout rates for clients. The current authors describe a structured, four-session treatment protocol that integrates the tenets of Externalizing Metaphors Therapy (EMT) with Innovative Moments (IMs) in addressing anxiety for children and youth. EMT is based upon the externalization of problems, transformation of metaphoric imagery, and the shifting of underlying maladaptive emotional schemas. It is suggested that treatment outcomes are enhanced through the integration of three IMs between-session exercises.